Biosynthesis, Chemical Structure, and Structure-Activity Relationship of Orfamide Lipopeptides Produced by Pseudomonas protegens and Related Species - Ma, Zongwang; Geudens, Niels; Kieu, Nam P.; Sinnaeve, Davy; Ongena, Marc; Martins, José C.; Höfte, Monica (Frontiers in Microbiology, 2016)
Orfamide-type cyclic lipopeptides (CLPs) are biosurfactants produced by Pseudomonas and involved in lysis of oomycete zoospores, biocontrol of Rhizoctonia and insecticidal activity against aphids. In this study we compared the biosynthesis, structural diversity, in vitro and in planta activities of orfamides produced by rhizosphere-derived Pseudomonas protegens and related Pseudomonas species. Genetic characterization together with chemical identification revealed that the main orfamide compound produced by the P. protegens group is orfamide A, while the related strains Pseudomonas sp. CMR5c and CMR12a produce orfamide B. Comparison of orfamide fingerprints led to the discovery of two new orfamide homologues (orfamide F and orfamide G) in Pseudomonas sp. CMR5c. The structures of these two CLPs were determined by nuclear magnetic resonance (NMR) and mass spectrometry (MS) analysis. Mutagenesis and complementation showed that orfamides determine the swarming motility of parental Pseudomonas sp. strain CMR5c and their production was regulated by luxR type regulators. Orfamide A and orfamide B differ only in the identity of a single amino acid, while orfamide B and orfamide G share the same amino acid sequence but differ in length of the fatty acid part. The biological activities of orfamide A, orfamide B and orfamide G were compared in further bioassays. The three compounds were equally active against Magnaporthe oryzae on rice, against Rhizoctonia solani AG 4-HGI in in vitro assays, and caused zoospore lysis of Phytophthora and Pythium. Furthermore we could show that orfamides decrease blast severity in rice plants by blocking appressorium formation in M. oryzae. Taken all together, our study shows that orfamides produced by P. protegens and related species have potential in biological control of a broad spectrum of fungal plant pathogens.